The Influence of the Quantum Teaching Learning Model Assisted by Audio Visual Media on Poetry Writing Skills - Rista Amameli Kartika; Andri Pitoyo; Marista Dwi Rahmayantis (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) poetry writing skills of class XI students of SMA Negeri 3 Kediri without using the Quantum Teaching model assisted by audiovisual; 2) poetry writing skills using the Quantum Teaching model assisted by audiovisual media in class XI students of SMA Negeri 3 Kediri; 3) the effect of using the Quantum Teaching model assisted by audiovisual media on poetry writing skills of class XI students of SMA Negeri 3 Kediri. This study uses a quantitative method with an experimental design. The study took place in the even semester of the 2024/2025 academic year. The research subjects consisted of two groups, namely class XI-1 students as the experimental group and class XI-2 students as the control group. Data were obtained through a written poetry writing test. Data were analyzed using descriptive and inferential statistics, namely the independent sample t-test preceded by a normality test and a homogeneity test of population variation. The results of the study: 1) poetry writing skills of class XI students of SMA Negeri 3 Kediri without using the Quantum Teaching model assisted by audiovisual are classified as low; 2) the poetry writing skills using the Quantum Teaching model assisted by audiovisual media in class XI students of SMA Negeri 3 Kediri are pretty high; 3) there is an influence in the use of the Quantum Teaching model assisted by audiovisual media on the poetry writing skills of class XI students of SMA Negeri 3 Kediri.